Biodegradable macroporous scaffold with nano-crystal surface microstructure for highly effective osteogenesis and vascularization. Issue 11 (1st March 2018) - Chu, Linyang; Jiang, Guoqiang; Hu, Xi-Le; James, Tony D.; He, Xiao-Peng; Li, Yaping; Tang, Tingting
Abstract : We report the construction of a biodegradable macroporous scaffold with a nano-crystal surface microstructure capable of releasing bioactive ions for highly effective osteogenesis and vascularization. Abstract : Using the hydrothermal calcination method, bovine cancellous bone was transformed into a degradable macroporous scaffold with a nano-crystal surface microstructure, capable of releasing bioactive ions. Compared with the control group, the presence of the nano-crystal microstructure of the material scaffold significantly promoted the gene expression of adhesion proteins including integrin and vinculin, thus facilitating attachment, spreading, proliferation and focal adhesion formation of MC3T3-E1 cells on the surface of the scaffold. Additionally, the release of active magnesium and calcium ions from the scaffold promoted expression of osteogenic genes and formation of calcium nodules in osteoblasts. Both in vitro and in vivo assays demonstrated that the three-dimensional interconnected porous architecture promoted vascularization and tissue integration. Our findings provide new insight into the development of degradable macroporous composite materials with "three-dimensional" surface microstructures as bone substitutes or tissue engineering scaffolds with potential for clinical applications.